KONSENTRASI HAMBAT MINIMUM FRAKSI BIOAKTIF RIMPANG TEMULAWAK TERHADAP JAMUR Candida albicans - Trimin Kartika; Dewi Novianti (Biota, 2018)
Candida albicans is a microbiota in the human body that is opportunistic. The infection caused by C.albicans is called candidiasis. People in some areas in Indonesia take advantage of rhizome temulawak for the traditional treatment of various diseases such as whiteness. The objective of the study was to determine the Minimum Barrier Concentration of active fraction of methanol extract of temulawak rhizome on Candida albicans. The ginger rhizomes were extracted in stages using soxhlet, then fractionation was done using Liquid Chromatography (KCV) method after the active fraction was then determined the minimum inhibitory concentration of the active fraction against C.albicans. The result showed that the minimum inhibitory concentration of the active fraction of temulawak rhizome was 62,5 μg / ml to C.albicans. The KHM value of 125 μg/ml is included in a very strong antifungal activity meaning that the temulawak rhizome has good potential to be a phytopharmaca.